What Do Children Want to Read? A Case Study of How One Primary School Library Supported Reading for Pleasure. Issue 7 (3rd October 2022) - Loh, Chin Ee; Gan, Sujia; Mounsey, Sarah
Abstract: In a landscape where children report that they enjoy reading less, parents, educators and policymakers are increasingly concerned about how to engage children in reading for pleasure. School libraries are core spaces for encouraging reading for pleasure. This mixed-methods case study examines the reading choices and preferences of students in one primary school to understand what children read, how their reading tastes change across the primary years, and how the school library supports their reading for pleasure. Findings showed a shift in children's reading tastes across the years as they mature in their reading and interests. Children engage in repeated reading and the multiple reading of many books, series books, and comics remain popular, and recommendations are a key strategy for children to discover new reads. Two key priorities for school libraries keen to promote reading for pleasure emerge: building a contemporary book collection in school libraries that is interesting to children's similar and diverse tastes and creating opportunities for children to find new materials to pique their interest in reading.